2021
DOI: 10.1186/s12872-021-02233-w
|View full text |Cite
|
Sign up to set email alerts
|

Resistance exercise affects catheter-related thrombosis in rats through miR-92a-3p, oxidative stress and the MAPK/NF-κB pathway

Abstract: Background MiR-92a-3p and oxidative stress are associated with catheter-related thrombosis (CRT). As a kind of physical intervention, resistance exercise can effectively promote blood circulation. In this study, we investigated the roles of miR-92a-3p, oxidative stress and the P38 mitogen-activated protein kinase/nuclear factor-κB (MAPK/NF-κB) pathway in CRT during resistance exercise. Methods The rat CRT model was used for resistance exercise inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Studies have demonstrated that a sustained increase in reactive oxygen species can activate inflammatory reactions by activating MAPK signaling pathways. This activation leads to apoptosis of vascular endothelial cells and induces thrombosis [ 83 ]. Furthermore, studies have shown that ginsenoside-Rp3 can regulate MAPK signaling pathways to inhibit platelet activation and thrombosis [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that a sustained increase in reactive oxygen species can activate inflammatory reactions by activating MAPK signaling pathways. This activation leads to apoptosis of vascular endothelial cells and induces thrombosis [ 83 ]. Furthermore, studies have shown that ginsenoside-Rp3 can regulate MAPK signaling pathways to inhibit platelet activation and thrombosis [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we also observed downregulation of EV miR-92a-3p and miR-27a-3p in TR compared to IN individuals. As reported by Wen and colleagues ([ 50 ], p. 3), the reduction in circulating miR-92a-3p may be induced by resistance exercise intervention that leads to a decreased oxidative stress response. This mechanism seems to be related to a reduction of miR-92a-3p-mediated repression of HO-1 (HMOX1), an antioxidant enzyme found in vascular endothelial cells and smooth muscle cells.…”
Section: Discussionmentioning
confidence: 78%
“…In normal cases, NF-кB is ubiquitously present in various tissue cells in an inactive state. In response to stimulation with activators (e.g., proinflammatory cytokine, Toll-like receptor, p38-MAPK, HO-1, and ROS), NF-κB dimers will be released to nucleus to regulate target gene expression, inducing the body’s immune and inflammatory responses [ 34 ]. Multiple studies have proved that DKD development is associated with NF-κB hyper-activation.…”
Section: Oxidative Stress In Pathogenesis Of Dkdmentioning
confidence: 99%